Liberal Versus Restrictive Transfusion Trigger after Acute Brain Injury: More than Just Higher Blood Oxygen Content - Adrienne K. Ho (Neurotrauma Reports)
Previous studies on restrictive versus liberal blood hemoglobin transfusion triggers in critically ill or cardiac surgery patients had established a paradigm favoring restrictive triggers. In contrast, the hemoglobin transfusion threshold in traumatic brain injury optimization and transfusion strategy in patients with acute brain injury trials (2024) suggest that a liberal hemoglobin (90–100 g/L) transfusion trigger is associated with better neuro-outcomes than a restrictive (70 g/L) trigger in anemic patients with acute brain injury. Increased blood oxygen content is one obvious possible reason for the observed superior neuro-outcomes with more liberal red blood cell transfusion. In this author’s opinion, another plausible reason is that in replacing extracranial blood loss, which most of the patients in both trials had, avoidance of blood alternatives that could worsen intracranial hypertension might also have benefitted the liberal transfusion cohorts.